ANALYSIS OF LOCAL FINANCIAL INDEPENDENCE CHALLENGES MODERATED BY ECONOMIC GROWTH (CASE STUDY OF PROVINCES REGENCIES/CITIES IN KALIMANTAN) - Anjani, Rija; Masnila, Nelly; Yanto, Desri (Jurnal Akuntansi dan Keuangan (JAK), 2025)
This research was aimed to analyze the influence of local taxes, revenue sharing, and capital expenditure on the independence of local government finances in the support of the implementation of autonomy by the government, using economic growth as a moderating variable. Using secondary data from financial audit reports on 56 districts/cities in Kalimantan over five years with 280 observations. The analysis method employs panel data, Moderated Regression Analysis (MRA), and hypothesis testing using Eviews 12.The results showed that local taxes have a significantly positive effect on local financial independence, while the sharing of revenue and expenditure of capital have a significant negative effect on local financial independence. Economic growth positively and significantly affects the relationship between local taxes and financial independence, while negatively and significantly affects the relationship between capital expenditure and financial independence, and economic growth is not able to moderate the relationship between revenue sharing to financial independence. Overall, economic growth has a significant role in moderating the effect of these variables used in Kalimantan districts/cities during the study period.